SOSIALISASI PENGENALAN DAN PENERAPAN INTERNET OF THING (IOT) DI ERA REVOLUSI INDUSTRI 4.0 - Badriah Nursakinah; Octaviana Anugrah Ade Purnama (Abdi Jurnal Publikasi, 2023)
Advances in technology not only facilitate human work, but can also reduce human involvement in an activity. If in the past we knew that the minimum factors of production consisted of man, machine, material, money, and method (5M), then in the current era of the industrial revolution 4.0 it is possible that the role of the factor of production in the form of labor will be very minimal because some will be taken over by machines. According to the forecast from the prediction of the PWC consultant (Price Waterhouse Cooper) in 2030 almost half of human work will be diverted to automation machines where the use of robots will be used as a tool for human work. With that, the sophistication of Industry 4.0 is enough to have an extraordinary impact. An example that we often see is that applications such as Google Translate and Youtube are now able to detect voices which will automatically create subtitles from the sound produced (speech to text). This kind of sophistication will greatly save time at work if we know how to use it. From this, we can realize that HR needs will be more efficient because working hours can be more optimal to do other work. Internet Of Thing (IoT) is not the name of a specific hardware, software or platform. IoT is actually a term that describes a collection of software and other technologies with the aim of exchanging data with devices consisting of sensors, devices and other systems via the internet. In other words, the idea is to make all the objects around us stream useful data to the internet, so it's called the Internet of Things (Internetting everything).